Randomized Controlled Trial of Paliperidone Extended Release Versus Risperidone for the Treatment of Methamphetamine-Associated Psychosis in Chinese Patients - Wang, Gang; Ding, Fan; Chawarski, Marek Cezary; Hao, Wei; Liu, Xuebing; Deng, Qijian; Ouyang, Xuan (Frontiers in Psychiatry, 2020)
Background: The efficacy or tolerability of paliperidone extended release (ER) in the treatment of methamphetamine (METH)-associated psychosis (MAP) is unknown. This study was designed to assess the tolerability and efficacy of paliperidone ER and risperidone for the treatment of MAP in China. Methods: This 25-day randomized clinical trial involved 120 patients with acute MAP symptoms who were randomized to receive either paliperidone ER or risperidone from baseline to day 25 of an inpatient hospital stay. The primary outcome was changes in the severity of psychosis, which were assessed using the Positive and Negative Syndrome Scale (PANSS) total score changes from baseline to endpoint. Results: Overall, 84% of the patients completed the entire study protocol. The PANSS total score, the Clinical Global Impressions-Severity of Illness scale (CGI-S) score, and a METH craving score assessed by a visual analog scale (VAS) showed statistically significant improvements from baseline for the patients in both groups (p<0.01). The Simpson-Angus Scale (SAS) and the Barnes Akathisia Rating Scale (BARS) scores increased from baseline during treatment in both groups (p<0.01); there were statistically significant differences between the treatment groups in the SAS scores (p<0.01). Measures of hypermyotonia, salivation, and dizziness were significantly higher in the risperidone-treated patients than in the paliperidone ER-treated patients (all p<0.05). Conclusion: Paliperidone ER and risperidone had similar efficacy and were generally tolerable in the treatment of MAP; however, paliperidone ER had a more favorable adverse event profile than risperidone, particularly regarding extrapyramidal and prolactin-increasing effects.